Nestor, Barbara (audio interview #8 of 10) - Nestor, Barbara (9/29/1884 - 11/1/1979); Berger Gluck, Sherna, interviewer
INTERVIEW DESCRIPTION - This is the seventh interview with Barbara Nestor, a former member of the Communist Party. The audio quality of the interview is fair, and there are a segments in which several skips occur. 1/2/1975